1993
DOI: 10.1038/366158a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of Ca2+ selectivity and ion permeation in L-type Ca2+ channels

Abstract: Voltage-gated Ca2+ channels link changes in membrane potential to the delivery of Ca2+, a key second messenger for many cellular responses. Ca2+ channels show selectivity for Ca2+ over more plentiful ions such as Na+ or K+ by virtue of their high-affinity binding of Ca2+ within the pore. It has been suggested that this binding involves four conserved glutamate residues in equivalent positions in the putative pore-lining regions of repeats I-IV in the Ca2+ channel a1 subunit. We have carried out a systematic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
509
1
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(553 citation statements)
references
References 26 publications
39
509
1
3
Order By: Relevance
“…The inability of the Ca V 1.2 4EQ channel to rescue the Ca V 1.2 morpholino effects ( Figure 3, A and C) and the smaller jaws observed after pharmacologic blockade of Ca V 1.2 with nisoldipine ( Figure 3, D and E) provide additional evidence that mandibular development depends directly on Ca 2+ influx through Ca V 1.2. Dihydropyridines have not been shown to disrupt the Ca V 1.2 macromolecular complex, and the Ca V 1.2 4EQ channel remains a voltage-sensitive cation channel -though one that is not able to permeate Ca 2+ due to loss of the high-affinity binding site in the pore (11). Thus, we conclude that functions other than Ca 2+ permeation are unlikely to contribute to the Ca V 1.2-dependent regulation of mandibular development.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The inability of the Ca V 1.2 4EQ channel to rescue the Ca V 1.2 morpholino effects ( Figure 3, A and C) and the smaller jaws observed after pharmacologic blockade of Ca V 1.2 with nisoldipine ( Figure 3, D and E) provide additional evidence that mandibular development depends directly on Ca 2+ influx through Ca V 1.2. Dihydropyridines have not been shown to disrupt the Ca V 1.2 macromolecular complex, and the Ca V 1.2 4EQ channel remains a voltage-sensitive cation channel -though one that is not able to permeate Ca 2+ due to loss of the high-affinity binding site in the pore (11). Thus, we conclude that functions other than Ca 2+ permeation are unlikely to contribute to the Ca V 1.2-dependent regulation of mandibular development.…”
Section: Discussionmentioning
confidence: 83%
“…We next tested whether jaw development depended upon Ca 2+ influx through Ca V 1.2 with a Ca 2+ -impermeant rabbit Ca V 1.2, in which 4 key aspartate residues in the channel's poreforming α 1C subunit were mutated to glutamine. This 4EQ mutant (Ca V 1.2 4EQ ) retains its ability to scaffold other signaling proteins (e.g., auxiliary subunits) and to conduct ions, but completely blocks Ca 2+ permeation (11). Unlike Ca V 1.2 WT or Ca V 1.2 TS , Ca V 1.2 4EQ did not restore mandible size when coinjected with the Ca V 1.2 knockdown morpholino cocktail ( Figure 3, A and C).…”
Section: Figurementioning
confidence: 95%
“…Consequently, part of the topological arrangement of the cq in motif IV is altered. The translation stops in the mutant mdg oq after the motif IV SS 1 region and the critical SS2 segment that carries glutamic acid residues important for Ca 2+ selectivity are missing [24][25][26]. Further, the IVS 6 and the C-terminal tail are deleted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, in the mutant protein part of the IVSS 1, the IVSS2, the extracellular connecting loop to IVS6, the IVS 6 and the entire C-terminal cytoplasmic tail is missing. Some of these segments, in particular the IVSS1 and IVSS2, are well-identified integral components of the high-affinity Ca 2+ filtration units [24][25][26]; the putative E-F hand [27] on the Cterminal tail may also be involved in Ca 2+ binding. Based on hydropathy analysis and prediction of secondary structure, we suggest that the C-terminus of the mutant protein will be largely globular and localized intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…In K + -selective channels (31), voltage-dependent Na + (32) and Ca 2+ channels (33), cyclic-nucleotide-gated channels (34), and ClC Cl -channels (35), for example, the identity of these chemical groups has been firmly established on the basis of electrophysiological and/or X-ray crystallographical observations. In pLGICs, in GLIC (PDB code 4HFI) GLIC (PDB code 4HFI) α1 GluCl (PDB code 3RHW) 1 GluCl (PDB code 3RHW) contrast, although the sequence conservation and pore location of the oppositely charged side chains at positions -1′ and 0′ may have suggested that they are the main contributors to charge selectivity, the experimental data recorded before this work had failed to provide compelling evidence for this idea.…”
Section: Discussionmentioning
confidence: 99%